Excavations at Jebel Faya — The FAY-NE1 shelter sequence - Bretzke, Knut; Conard, Nicholas J.; Uerpmann, Hans-Peter (Proceedings of the Seminar for Arabian Studies, 2014)
We report here on layers and finds from Faya Shelter, an archaeological sequence excavated in the south-western part of site FAYNE1 at Jebel Faya in the Central Region of Sharjah Emirate. Work between 2009 and 2013 exposed six archaeological horizons (AHs) and enabled a stratigraphie connection of AHs IV-VI from Faya Shelter with assemblages A, B, and C from the recently published Faya Terrace sequence. No stratigraphic correlation with the terrace sequence is possible for AH I-AH III. While the number of artefacts in AHs I and III is currently too small to gain meaningful characterizations of lithic assemblages, AHs II, IV, V, and VI add important data to the record of Late Pleistocene archaeology in south-east Arabia. Lithic technology in AH II is characterized by reduction from flat cores with opposed platforms and an emphasis on the production of blades often using soft-hammer percussion and platform faceting. AH IV is characterized by the production of flakes from multiple platform cores with plain striking platforms using hard-hammer percussion. Striking characteristics of the lithic assemblage from AH V are the production of elongated flakes and cores with orthogonal scar pattern. In contrast, the lithic artefacts in AH VI indicate the use of centripetal Levallois and bifacial reduction. Flakes with large and unprepared striking platforms in addition to pronounced bulbs of percussion indicate hard-hammer percussion. Archaeological assemblages from Faya Shelter indicate differences in the cultural background of Jebel Faya’s inhabitants. Given that hunter-gatherer groups would not be able to settle at Faya during periods of desiccation, the discontinuous cultural sequence from Faya Shelter indicates a complex pattern of connections between Faya and adjacent regions in southern Arabia and outside Arabia.